The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.envpol.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of rates and controls on elemental mercury evasion in the Great Lakes Basin

Abstract: Rates of surface-air elemental mercury (Hg o ) fluxes in the literature were synthesized for the Great Lakes Basin (GLB). For the majority of surfaces, fluxes were net positive (evasion).Digital land-cover data were combined with representative evasion rates and used to estimate annual Hg o evasion for the GLB (7.7 Mg/yr). This value is less than our estimate of total Hg deposition to the area (15.9 Mg/yr), suggesting the GLB is a net sink for atmospheric Hg. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Several studies have suggested that atmospheric Hg 0 is the primary form of Hg that is incorporated into leaf tissue (Rea et al, 2002;Ericksen et al, 2003;Bushey et al, 2008), and Hg 0 is estimated to make up almost 60% of anthropogenic atmospheric emissions of Hg in the northeastern United States Denkenberger et al, 2012). Hg 0 is also relatively stable in the atmosphere and capable of being transported long distances from sources (Fitzgerald et al, 1998;Driscoll et al, 2013).…”
Section: Geographic Patterns Of Mercury Depositionmentioning
confidence: 99%
“…Several studies have suggested that atmospheric Hg 0 is the primary form of Hg that is incorporated into leaf tissue (Rea et al, 2002;Ericksen et al, 2003;Bushey et al, 2008), and Hg 0 is estimated to make up almost 60% of anthropogenic atmospheric emissions of Hg in the northeastern United States Denkenberger et al, 2012). Hg 0 is also relatively stable in the atmosphere and capable of being transported long distances from sources (Fitzgerald et al, 1998;Driscoll et al, 2013).…”
Section: Geographic Patterns Of Mercury Depositionmentioning
confidence: 99%
“…The considerable discrepancy between the current total pools of soil Hg and the possible atmospheric Hg inputs over the period of soil formation (e.g., for 15k years, 140 mg/m 2 ) might be explained by the different immobilization capacities of soil at different stages of formation. A large fraction of deposited Hg is currently evaded back to the atmosphere (Denkenberger et al 2011). Conditions that affect the dynamics of SOM, which include climate, land-use change, and landscape disturbance therefore are likely, to a large extent, drive the spatial patterns of concentrations and pools of soil Hg.…”
Section: Pools and Turnovermentioning
confidence: 99%
“…In forest ecosystems, overstory canopies substantially enhance atmospheric Hg deposition via litterfall and throughfall deposition (St. Louis et al 2001, Demers et al 2007, Risch et al 2011. Elemental Hg (Hg 0 ) can be volatilized from land and water into the atmosphere, thus the transfer of Hg between the atmosphere and Earth surfaces is bidirectional (Denkenberger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…29,42 Similarly, the magnitude of fluxes measured at this site were within the typical range of North American background forests (0 to 1.4 ng m −2 h −1 ). 43 In contrast, the daily average fluxes measured near the HBMS smelter during its operation showed net Hg 0 deposition: −3.8 ng m −2 h −1 ( Figure 4B). This is noteworthy because the soil had a much higher Hg concentration (75 μg g −1 ) compared to that of the background reference location (0.20 ± 0.05 μg g −1 ) where net emissions were measured.…”
Section: Environmental Science and Technologymentioning
confidence: 86%
“…Applying an average literature value for emissions from boreal forest waterbodies (0.9 ng m −2 h −1 ) 43 and adding this to the soil emissions results in a total landscape flux of 95 kg per year within the 50 km radius of the smelter. Applying a background waterbody flux value for this region is consistent with data showing that the water Hg concentrations in the Flin 49 The emissions from the high-Hg-content soils close to the smelter had much higher average fluxes compared to the fluxes over the entire impacted area (the mean flux within a 4 km radius of smelter was 29 ± 10 ng m −2 h −1 compared to the mean within 50 km of the smelter, 1.8 ± 0.6 ng m −2 h −1 ).…”
Section: Environmental Science and Technologymentioning
confidence: 99%